Analisis Dinamika Sosial dan Ekonomi Pelaku Kasus Perjudian Online dalam Sudut Pandang Money Laundry - Ciek Julyati Hisyam; Indah Permatasari; Tauliah Puji Lestari; Yola Medistya; Putra Nizar Pratama; Aisyah Haura Firdaus; Alexander Dimas Adi Prakoso (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Online gambling has become a rapidly growing social issue supported by advancements in digital technology, particularly in Indonesia, with its large population of internet users. Despite being legally prohibited, its popularity continues to rise, creating challenges for law enforcement and significant socio-economic impacts. This study aims to analyze the social and economic dynamics of online gambling actors using a descriptive qualitative method. Data were collected through in-depth interviews and document analysis, then analyzed using thematic coding techniques. The findings reveal that actors, such as Koh Jimmy, learn deviant behaviors through exclusive online communities that provide operational techniques and moral justification. Economic motivation, social support, and gambling systems designed to induce addiction are key drivers of actor involvement. Although aware of legal risks, actors remain engaged due to community influence and substantial financial gains. This study underscores the relevance of differential association theory in explaining actor involvement in online gambling and provides recommendations for preventive policies through technological oversight, social education, and the strengthening of social norms. The results are expected to serve as a foundation for formulating more effective preventive and intervention measures.